Queen bees solving N-Queens problem using ABC algorithm - Daria, Airene Louise B. (2011)
The N-Queens problem has been present for over a century and had caught the attention of several mathematicians, game enthusiasts and computer scientists. The problem aims in placing N queens in an N by N board where no two or more queens attack each other as governed by the rules in the famous board game chess. Another swarm based intelligence algorithm which mimics the intelligent behavior of bees in food foraging is used in coming up with a single solution from a family of solutions given a certain number N. In this study, an implementation of the Artificial Bee Colony algorithm is presented to solve the N-Queens problem. The results then showed the effectiveness of the algorithm in solving the N-queens problem with values for N ranging from 4 to 1000.